Exploring Confucian culture's impact on corporate debt default risk: an ethical decision-making approach - Zhang, Ning (Journal of business ethics, 2025)
Corporate debt default risk poses significant challenges in the business world, requiring a multifaceted approach for effective mitigation. This study, grounded in an ethical decision-making framework, investigates the influence of Confucian culture on shaping ethical corporate culture and managers’ moral capacity and its subsequent impact on corporate debt default risk. Our findings indicate that companies deeply influenced by Confucian culture tend to exhibit lower debt default risks. Specifically, companies that embrace Confucian values demonstrate an enhanced ethical corporate culture and heightened individual moral capacity. These factors play crucial roles in the ethical decision-making process, thereby reducing the likelihood of engaging in risky financial behaviors. Further analysis reveals that the inhibitory effect of Confucian culture on debt default risk is particularly pronounced in enterprises operating within regions characterized by poor integrity environments and weak product market competition. This inhibitory effect can lead to a reduction in the cost of corporate debt financing and the risk of stock price crashes. Overall, this study contributes to the understanding of the interplay between culture, business ethics, and corporate risk management.